Glyceriformia (Annelida) of the abyssal SW Atlantic and additional material from the SE Atlantic - Böggemann, Markus (Marine Biodiversity, 2016)
Four species of Glyceridae (Glycera capitata, Glycera diva, Glycera southeastatlantica, Glycera tesselata) and three species of Goniadidae (Bathyglycinde profunda, Goniada cf. maculata, Progoniada regularis) were collected during the DIVA-3 deep sea cruise in 2009 to the south-western sector of the Atlantic Ocean (Argentinean and Brazilian basins). An identification key to the Glyceriformia is presented with detailed and illustrated morphological descriptions given for all species. Furthermore, additional raw material from the DIVA-1 (2000) and DIVA-2 (2005) expeditions to abyssal zones of the SE Atlantic are also included.
World Polychaeta Database (WPolyDb)